USE OF DIGITAL X-RAY TOMOSYNTHESIS TECHNOLOGY FOR DETECTION OF COMBAT INJURIES - Khobta, Yurii; Miroshnychenko, Sergii; Miroshnychenko, Oleksandra (Science-based technologies, 2025)
Modern combat operations are characterized by the massive use of shrapnel explosive parts both in drones and in aviation and artillery cluster munitions. This causes a large number of combat injuries and injuries of a shrapnel nature. There are several types of pathologies caused by shrapnel lesions that require instrumental diagnostics, the main ones being: shrapnel stuck in the body of the wounded and marginal fracture. Considering that body armor and helmets provide protection for the torso and head of combatants, while the limbs remain unprotected, which causes a significant percentage of shrapnel injuries to these parts of the body. To assess the informativeness of radiological diagnostics of pathologies, use such indicators as diagnostic sensitivity and specificity. Unfortunately, in the conditions of modern hostilities, the possibility of using stationary and X-ray tomographs in medical sorting points and field hospitals is extremely limited. In these places, mobile digital X-ray machines are used, which have already proven their feasibility and necessity. According to existing estimates, in various applications for medical diagnostics, X-ray has a sensitivity of 0.35...0.45, that is, 2..3 times less than computed tomography. The lack of experienced diagnosticians and the impossibility of quickly training new ones requires increasing the level of diagnostic equipment of field hospitals with medical equipment with a high level of diagnostic sensitivity. In X-ray images, the layer with pathology and layers of bone tissue overlap, which reduces the contrast of the pathology. Irradiation of the object at different angles is the basis of X-ray examination using tomographic methods. The algorithm for obtaining diagnostic data in digital X-ray tomosynthesis systems is as follows. The X-ray tube moves within the scanning angle of +20 degrees, sending X-ray pulses that are synchronized with the dynamic digital receiver (DDR), which records them. Depending on the system design, the receiver can stand still or move in the opposite direction to the movement of the X-ray tube. The examined object (patient) is in this case within the projection formation zone. At this stage, a sequence of 60...120 X-ray images (projections) is formed. After obtaining the entire series of projections, at the second stage, tomographic reconstruction of 100...300 images of slices parallel to the plane of the receiver is performed. Contrasts of pathologies in images with tomosynthesis depend on the difference in X-ray density of pathologies and intact tissues, as well as on the thickness of the layers. For tomosynthesis images, the maximum contrast occurs in the layer where the pathology is. In other layers, a defocused and weakened image of the pathology is observed, which sharply reduces their impact. Using the tomosynthesis mode almost eliminates the visual loss of pathology in the image and allows even moderately trained personnel to confidently diagnose at the advanced stages of medical evacuation.